2010
DOI: 10.1177/0093650210391655
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Conflict Behavior and Relational Satisfaction in Adult Parent–Child Relationships

Abstract: Dyadic data were used to examine associations between attachment, relational satisfaction, and perceptions of conflict style in adult child-parent relationships. Several actor effects emerged; secure attachment was associated with more collaborating and compromising, dismissive attachment was associated with less collaborating and more indirect fighting and avoiding, and preoccupied attachment was associated with more competitive and indirect fighting. There were also partner effects. Individuals were more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“…In addition, several studies have demonstrated links between parental attachment styles and parent- and child-reported parental behavior with college-aged children (e.g., J. Feeney, 2002, 2006; Kilmann et al, 2009; La Valley & Guerrero, 2012). Thus, additional studies are needed to clarify the nature of these links and explore the four possibilities outlined above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies have demonstrated links between parental attachment styles and parent- and child-reported parental behavior with college-aged children (e.g., J. Feeney, 2002, 2006; Kilmann et al, 2009; La Valley & Guerrero, 2012). Thus, additional studies are needed to clarify the nature of these links and explore the four possibilities outlined above.…”
Section: Discussionmentioning
confidence: 99%
“…Feeney, 2006), and as possessing less knowledge about their whereabouts and activities (Jones, Ehrlich, Lejuez, & Cassidy, 2014). In addition, parental security is positively related to college-aged children’s reports of satisfaction with the parent-child relationship (La Valley & Guerrero, 2012). Although these initial findings are intriguing, more research is needed to better understand the link between parental attachment styles and child perceptions of parents and how these perceptions relate to child behavior and adjustment.…”
Section: Parental Attachment Style and Child Behavior Toward And Percmentioning
confidence: 99%
“…Contrary to expectation, Lau and Peterson (2011) found no significant association between attachment style and parental satisfaction. Finally, La Valley and Guerrero (2010) found that security was related to greater parental satisfaction.…”
Section: Review and Analysis Of The Empirical Evidencementioning
confidence: 96%
“…In addition, two studies found that insecure parental attachment styles were related to less supportive and constructive parental behavior during parent-child conflicts (e.g., more anger and yelling, less problem-solving, and less collaborating; J. Feeney, 2006; La Valley & Guerrero, 2010). J. Feeney found that the links between attachment style and conflict behavior were somewhat different for mothers and fathers.…”
Section: Review and Analysis Of The Empirical Evidencementioning
confidence: 99%
“…Only a few studies have examined specific conflict styles in relation to parent–adolescent relationship satisfaction. Children were more satisfied with the quality of the relationship when using a compromising or complying conflict style (Zhang, ), whereas destructive styles characterized by a demand–withdraw interaction were associated with lower relationship satisfaction for both parents and adolescents (Caughlin & Malis, ; La Valley & Guerrero, ). In a daily diary study by Van Doorn, Branje, Hox, and Meeus (), adolescents' relationship satisfaction with mothers was greater on days with constructive conflicts than on days with destructive conflicts.…”
Section: Constellations Of Adolescents' and Mothers' Conflict Managemmentioning
confidence: 99%